From design to action: participatory approach to capacity building needs for local overdose response plans - Maryam Mallakin; Christina Dery; Yordanos Woldemariam; Michael Hamilton; Kim Corace; Bernie Pauly; Triti Khorasheh; Caroline Bennett AbuAyyash; Pamela Leece; Katherine Sellen (BMC, 2023)
Abstract Background In response to the rise in opioid-related deaths, communities across Ontario have developed opioid or overdose response plans to address issues at the local level. Public Health Ontario (PHO) leads the Community Opioid / Overdose Capacity Building (COM-CAP) project, which aims to reduce overdose-related harms at the community level by working with communities to identify, develop, and evaluate capacity building supports for local needs around overdose planning. The 'From Design to Action' co-design workshop used a participatory design approach to engage communities in identifying the requirements for capacity building support. Methods A participatory approach (co-design) provided opportunity for collaborative discussion around capacity building needs at the community level. The co-design workshop included three structured collaborative activities to 1) prioritize scenarios that illustrated various challenges associated with community overdose response planning, 2) prioritize the challenges within each scenario and 3) prioritize the supports to address each of these challenges. It was conducted with fifty-two participants involved in opioid/overdose-related response plans in Ontario. Participatory materials were informed by the results of a situational assessment (SA) data gathering process, including survey, interview, and focus group data. A voting system, including dot stickers and discussion notes, was applied to identify priority supports and delivery mechanisms. Results At the workshop, key challenges and top-priority supports were identified, for development and implementation. The prioritized challenges were organized into five categories of capacity building supports addressing: 1) stigma & equity; 2) trust-based relationships, consensus building & on-going communication; 3) knowledge development & on-going access to information and data; 4) tailored strategies and plan adaptation to changing structures and local context; and 5) structural enablers and responsive governance. Conclusion Using a participatory approach, the workshop provided an opportunity for sharing, generating, and mobilizing knowledge to address research-practice gaps at the community level for opioid response planning. The application of health design methods such as the 'From Design to Action' co-design workshop supports teams to gain a deeper understanding of needs for capacity building as well as illustrating the application of participatory approaches in identifying capacity building needs for complex public health issues such as the overdose crisis.